PSXVI-32 Evaluation of equine industry participation among young adults. (7th December 2018) - Martinez, R; Leatherwood, J; Walker, N; Much, M; Vogelsang, M
Abstract: The equine industry has identified a major limitation in maintaining participation of young adults in competitive events. In order to overcome this limitation, breed associations, such as the American Quarter Horse Association, have developed young adult subcommittees as part of their annual marketing and membership plans. Although there is an apparent disconnect in this age group, no data have been provided relating to the activity level of these young adults as they transition out of their youth career to amateur or professional status. Therefore, the objective of this study was to quantify the number of young adults that participate in various competitive events. Students enrolled in four senior level courses at Texas A&M University (College Station, TX), Equine Nutrition (74), Issues in the Equine Industry (70), Equine Production and Management (78) and Equine Disease and Epidemiology (107), completed an online survey. A total of 194 (58.96% response rate) (25 males and 169 females; 19 to 33 yr) responses were obtained using online data collection software (Qualtrics, Provo, UT). Students identified growing up predominantly in a suburban (50.52%) or rural (36.60%) environment and participated in competitive events (45.88%) or recreational riding (23.71%) throughout high school. While in college, 75.77% of students indicated that they do not compete with their personal horses. Of the 24.23% of students competing on their personal horses, 8.75% participate in breed-sanctioned events, with an additional 3.33% to 4.17% competing in specialized disciplines at the state or national level, respectively. The students that do compete, often compete monthly (10.82%) or biannually (9.28%). These data indicate that there is a decrease in the number of young adults participating in competitive events with their personal horse. Equine organizations will need to develop incentives to retain membership and participation of these young adults to encourage life-long involvement.